PENGARUH PERILAKU KEPEMIMPINAN KEPALA SEKOLAH DAN BUDAYA ORGANISASI TERHADAP KINERJA GURU PENDIDIKAN AGAMA ISLAM DI SD, SMP, SMA DAN SMK SE KABUPATEN FAKFAK - Zainuddin Zainuddin (LISAN AL-HAL: Jurnal Pengembangan Pemikiran dan Kebudayaan, 2017)
Leadership behavior is individual behavior a leader (Principal) which directs group activities to achieve common goals. Organization culture refers to a system of all meaning shared by members that is distinguishes from other organizations, this system of all meaning, when observe is a set of key characteristics appreciated by the organization. The Islamic Education Teachers Performance is achievements that achieved by a teacher of Islamic Education in carrying out duties for a certain period According to competency standards and predefined criteria. The Influence of Leadership Behavior Principal and Organization Behavior can have an effect on Islamic education teacher performance. The purpose of studies are (1) Explain the level of leadership behavior, organizational culture, and Islamic education teacher performance, (2) Explain the influence of leadership behavior on Islamic Education teacher performance, (3) Explain the influence of organizational culture on teacher performance and (4) Explain the influence of leadership behavior, organization culture on Islamic education teacher performance at Fakfak. The results of data processing known that are (1) from 45 respondent more than 80% has agreement about the important of leadership behavior principle, organization culture and increasing teacher’s performance. (2) There are a positive and significant influence on leadership behavior, and organizing culture on the Islamic religious education teachers performance, explain data value is Fcount (82,142) >Ftable 3,219 significance 0.000< 0,005, (3) There are positive influence and significance leadership behavior on Islamic religious education teachers performance, its show on value of counted (7,460) > t-table 2,018 and significance t-test 0.000<0,005, (4) there are positive influence and significance organization culture on Islamic education teacher performance, its explain with data value t-count (3,451) > t-table2,018 and significance t-test 0.001<0,005, (5) There are positive influence and significance simultaneously leadership behavior, organization culture on Islamic education teacher in elementary school , junior high school and senior high school at Fakfak. The result of analysis test F with significance value 0.000 < 0,005. High R square is 0,787, its mean 78,7% and balance 21,3% effected by other variable in addition to two variables like leadership behavior and Organization behavior.